Equilibrium Analysis of Portfolio Insurance - Grossman, Sanford J.; Zhou, Zhongquan (Journal of Finance, 1996)
A martingale approach is used to characterize general equilibrium in the presence of portfolio insurance. Insurers sell to non-insurers in bad states, and general equilibrium requires that the risk premium rises to induce non-insurers to increase their holdings. We show that portfolio insurance increases price volatility, causes mean reversion in asset returns, raises the Sharpe ratio and volatility in bad states, and causes volatility to be correlated with volume. We also explain why out-of-the-money S&P 500 put options trade at a higher volatility than do in-the-money puts.